Oscillations of centroid position and surface area of soccer teams in small-sided games - Frencken, W.; Lemmink, K.; Delleman, N.; Visscher, C. (European Journal of Sport Science, 2011)
There is a need for a collective variable that captures the dynamics of team sports like soccer at match level. The centroid positions and surface areas of two soccer teams potentially describe the coordinated flow of attacking and defending in small-sided soccer games at team level. The aim of the present study was to identify an overall game pattern by establishing whether the proposed variables were linearly related between teams over the course of the game. In addition, we tried to identify patterns in the build-up of goals. A positive linear relation and a negative linear relation were hypothesized for the centroid positions and surface areas respectively. Finally, we hypothesized that deviations from these patterns are present in the build-up of goals. Ten young male elite soccer players (mean age 17.3, s=0.7) played three small-sided soccer games (4-a-side) of 8 minutes as part of their regular training routine. An innovative player tracking system, local position measurement (LPM), was used for obtaining player positions at 45 Hz per player. Pearson correlation coefficients were calculated to investigate the proposed linear relation of the key variables. Correlation coefficients indicate a strong positive linear relation during a whole game for the centroid position in all three games, with the strongest relation for the forward-backward direction (r>0.94). For 10 out of 19 goals a crossing of the centroids in this direction can be seen. No negative linear relation was found for surface area (-0.01 < r<0.07). From this study, we concluded that over the course of a whole small-sided game, the forward-backward motion of the centroids is most strongly linearly related. Furthermore, goals show a specific pattern in the forward-backward motion of the centroid. Therefore, surface area and particularly centroid position may provide a sound basis for a collective variable that captures the dynamics of attacking and defending in soccer at team level. Future research should develop these ideas further.